What's India's Beef with Meat? Hindu Orthopraxis and Food Transition in India Since the 1980s. Issue 2 (21st February 2020) - Ferry, Mathieu
Abstract : Does development affect food practices? The nutrition transition model correlates positively meat consumption levels with gross domestic product per capita, except in India. In this article, I analyze food diets in this country since the 1980s by mapping out households' practices in animal product consumption depending on their social positions. Applying multiple factor analysis on the Consumer Expenditures data of the National Sample Survey Office, I produce a relational model of food diet segmentation to overcome the dead ends of the nutrition transition model. Two structural dimensions are highlighted. The first one differentiates beef and nonbeef meat diets and relates to the symbolic capital of caste and religion. The second one opposes diets including animal products and without, depending on the amount of economic capital. The concept of temporal homology is introduced to show that the social structure remains stable over time. This denotes the importance of sociocultural norms in food practices rather than their weakening due to "modernization" and shows how these norms are key to understand food transitions beyond linear expectations drawn from economic development.